The role of gas emissions (He, Rn, and CO2) from fault zones in understanding fault and seismic activity - Li, Jiye; Liu, Zhaofei; Chen, Zhi; Gao, Yan; Hao, Yongmei; Gu, Hongbiao (Frontiers in Earth Science, 2024)
Active fault zones are critical pathways for the migration of deep fluids to the Earth’s surface, carrying gases such as He, Rn, and CO2 that provide evidence for the physical and chemical dynamics of the Earth’s interior. This review examines the geochemical characteristics of fault zone gases and their implications for understanding fault activity and seismic events. Fault zones with high activity levels exhibit significant gas release, and variations in soil and hot spring gas concentrations can serve as indicators of seismic activity. Changes in gas concentrations and isotopic ratios, particularly before and after earthquakes, reflect the dynamic interplay between deep-sourced and shallow-sourced fluids. Seismic-induced stress alterations enhance gas release along fault zones, leading to observable anomalies that can aid in earthquake monitoring and prediction. The study underscores the importance of isotope tracing in deciphering fluid sources, migration pathways, and the evolution of fault zones, providing valuable information for assessing tectonic activity and mitigating seismic risks.